Hydrogen oxidation reaction on platinum nanoparticles: understanding the kinetics of electrocatalytic reactions via “nano-impacts” - Jiao, X; Lin, C; Young, N; Batchelor-McAuley, C; Compton, R (American Chemical Society, 2016)
The kinetics of the hydrogen oxidation reaction (HOR) on platinum nanoparticles (PtNPs) is explored. The steady-state current for HOR on individual PtNPs is measured via the nanoimpact approach. Adopting the Tafel-Volmer mechanism, the adsorption rate constant for HOR on PtNPs is calculated as 0.020 ± 0.008 m s–1. The HOR is also studied on electrodes where PtNPs are immobilized via drop-casting on the supporting substrate prior to experimentation and the kinetic parameters contrasted with those from the nanoimpact experiments. The distinction in the kinetic parameters between the nanoimpact and the drop-casting approaches reveals that the measurement on an individual nanoparticle is required in order to correctly understand the electrochemical reaction catalyzed by nanoparticles, because the aggregation or loss of the nanoparticles drop-casted on the electrode leads to unavoidable errors in the measurement.